Plastic Dreams: consumption goals of Melissa collectors - Pépece, Olga Maria Coutinho (2012)
The purpose of this essay is to understand the behaviour of brand collectors and to identify the goal hierarchy behind it. Melissa was the brand used as study object.We performed a literature review and two surveys, qualitative and quantitative, with collectors of the brand. The Means-End Chain Model was used and the Hierarchical Value Map was outlined as a result of the likelihood of relationships between different “having”, “doing” and “being” goals answered by each interviewee. In the qualitative phase, it was discovered that, in order to characterize a Melissa collection, the consumer must take care and preserve items long after they have lost their original purpose, describing them affectionately and associating them to symbolic representations. The quantitative phase showed that the strongest life goals are the Search for Pleasure and for Modernity, and that one of the main concerns and consumption intention of the consumers is to “show they are in the know regarding trends”.